Adoption Behaviour of Saffron Growers in Pashtun Zarghon of Herat Province in Afghanistan (Indian Journal of Extension Education, 2015)
In Afghanistan, Saffron is one of the most important income and employment generating commercial crop, it occupies 700 hectares of land area. Saffron industry of the province is also improving the country’s economy. Forty per cent of net incomes of the nation come from saffron. Pashtun Zarghon distract of Herat province (Afghanistan) was purposively selected for the present investigation covering 6 villages and 120 respondents selected randomly. The study inferred that majority of respondents were of middle aged, illiterate, having joint family, larger family size, member of one organization, medium level of annual income, medium socio-economic status, mass media exposure, regular radio listener, TV viewer, occasional magazine reader, frequently participating in training programme and demonstration, seldom participating in field visit, group meeting, tours have high level of knowledge but found to be ignorant about some complex practices and to possess few adoption level as well. There was positive and significant correlation between selected independent variable under study viz. age, education, annual income, mass media exposure, knowledge and extent of adoption of saffron production technology.